Freezing of gait in Parkinson’s disease: pathophysiology, risk factors and treatments - Gao, Chao (Transl Neurodegener, 2020)
BACKGROUND: Freezing of gait (FOG) is a common, disabling symptom of Parkinson’s disease (PD), but the mechanisms and treatments of FOG remain great challenges for clinicians and researchers. The main focus of this review is to summarize the possible mechanisms underlying FOG, the risk factors for screening and predicting the onset of FOG, and the clinical trials involving various therapeutic strategies. In addition, the limitations and recommendations for future research design are also discussed. MAIN BODY: In the mechanism section, we briefly introduced the physiological process of gait control and hypotheses about the mechanism of FOG. In the risk factor section, gait disorders, PIGD phenotype, lower striatal DAT uptake were found to be independent risk factors of FOG with consistent evidence. In the treatment section, we summarized the clinical trials of pharmacological and non-pharmacological treatments. Despite the limited effectiveness of current medications for FOG, especially levodopa resistant FOG, there were some drugs that showed promise such as istradefylline and rasagiline. Non-pharmacological treatments encompass invasive brain and spinal cord stimulation, noninvasive repetitive transcranial magnetic stimulation (rTMS) or transcranial direct current stimulation (tDCS) and vagus nerve stimulation (VNS), and physiotherapeutic approaches including cues and other training strategies. Several novel therapeutic strategies seem to be effective, such as rTMS over supplementary motor area (SMA), dual-site DBS, spinal cord stimulation (SCS) and VNS. Of physiotherapy, wearable cueing devices seem to be generally effective and promising. CONCLUSION: FOG model hypotheses are helpful for better understanding and characterizing FOG and they provide clues for further research exploration. Several risk factors of FOG have been identified, but need combinatorial optimization for predicting FOG more precisely. Although firm conclusions cannot be drawn on therapeutic efficacy, the literature suggested that some therapeutic strategies showed promise.